2020
DOI: 10.1101/2020.03.27.009381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular architecture of the luminal ring of theXenopus laevisnuclear pore complex

Abstract: Nuclear pore complex (NPC) mediates the flow of substances between the nucleus and cytoplasm in eukaryotic cells. Here we report the cryo-electron tomography (cryo-ET) structure of the luminal ring (LR) of the NPC from Xenopus laevis oocyte. The observed key structural features of the LR are independently confirmed by single-particle cryo-electron microscopy (cryo-EM) analysis. The LR comprises eight butterfly-shaped subunits, each containing two symmetric wings. Each wing co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Rather strikingly, we captured CA tubes threading through NUP153 NuPOD rings, which may represent the scenario of capsid passing through the NPC when the central pore is of sufficient size ( Figure 6). Although it is thought that the diameter of the NPC channel is less than the width of an HIV-1 capsid, recent evidence has shown that the NPC possesses a degree of elasticity, and the central channel may expand under certain conditions (Mahamid et al, 2016;Zhang et al, 2020). Consistently, our data provide direct evidence that assembled capsid structures can pass through a nuclear pore-like channel ( Figure 3D).…”
Section: Discussionsupporting
confidence: 85%
“…Rather strikingly, we captured CA tubes threading through NUP153 NuPOD rings, which may represent the scenario of capsid passing through the NPC when the central pore is of sufficient size ( Figure 6). Although it is thought that the diameter of the NPC channel is less than the width of an HIV-1 capsid, recent evidence has shown that the NPC possesses a degree of elasticity, and the central channel may expand under certain conditions (Mahamid et al, 2016;Zhang et al, 2020). Consistently, our data provide direct evidence that assembled capsid structures can pass through a nuclear pore-like channel ( Figure 3D).…”
Section: Discussionsupporting
confidence: 85%
“…Cryo‐ET has provided insights into the structure and function of viruses [9–12,92–97], nuclear pore complexes [64,98–100], ribosomes [101–103], coated vesicles [104–109], nucleosome arrangement in chromatin [110], cytoskeletal elements [111–113], bacterial secretion systems [114–117], chemotaxis [118,119], flagellar motors [120], and S‐layers [121]. Obtaining information about the spatial arrangement of proteins by cryo‐ET has also found use in assessing protein denaturation at the air‐buffer interface for single‐particle analysis [122].…”
Section: Examplesmentioning
confidence: 99%
“…This means that simply tilting the grid can have substantial benefits to improving the reconstruction. Indeed, many experimental cases have already made practical use of tilts to solve the preferred orientation problem and resolve the structure of a macromolecular object of interest [14][15][16][17][18][19][20][21], including samples as small as 40 kDa [22], and as large as the ~100 mDa nuclear pore complex [23,24]. The sampling plots, and the SCF* values, now provide quantitative insight explaining the benefits observed through experiment.…”
Section: The Effects Of Tilting the Grid On The Sampling Distribution And The Scf Valuementioning
confidence: 99%